Religious Activities and Empowerment : Sustainable Livelihood Framework Approach In Enhancing The Desa Luworo Potencies - Achmad Room Fitrianto (Al-Ulum, 2017)
The marginality and governmental alignments are the two main issues in community development. The role of Tengkulak Rentenir, and Pengijon are significant in Luworo Village. Not only as a financial provider, they also play as connector among the peasant farmer and market. As a result the farmer receipts their selling agricultural productions below market prices. In order to support and giving additional value to their agricultural products an assistance program involving a female Islamic study group of Masjid Al-Hidayah conducted. The assistance activities conducted through SLF approach. The five phases of SLF are: identifying vulnerability; mapping the livelihood assets owned by the community; observing transforming structures and processes; and identifying livelihood strategies and formulating livelihood outcomes.